2008
DOI: 10.2134/jeq2007.0279
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Bioreactors and Deep Drain‐Pipe Installation to Reduce Nitrate Losses in Artificially Drained Fields

Abstract: Nitrate in water removed from fields by subsurface drain ('tile') systems is often at concentrations exceeding the 10 mg N L(-1) maximum contaminant level (MCL) set by the USEPA for drinking water and has been implicated in contributing to the hypoxia problem within the northern Gulf of Mexico. Because previous research shows that N fertilizer management alone is not sufficient for reducing NO(3) concentrations in subsurface drainage below the MCL, additional approaches are needed. In this field study, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 57 publications
(60 reference statements)
7
84
1
Order By: Relevance
“…Studies have shown that, using woodchips, NO 3 -N concentrations were reduced by 60% from 22.1 to 8.8 mg L -1 (Jaynes et al, 2008) and by 94% from 9.4 to 0.58 mg L -1 (Chichlowski, 2014). Our research confirms this finding; woodchips achieved the greatest reduction of all the additives, reducing NO 3 -N concentrations by 78%.…”
Section: Effects Of Additives In Trench Backfillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that, using woodchips, NO 3 -N concentrations were reduced by 60% from 22.1 to 8.8 mg L -1 (Jaynes et al, 2008) and by 94% from 9.4 to 0.58 mg L -1 (Chichlowski, 2014). Our research confirms this finding; woodchips achieved the greatest reduction of all the additives, reducing NO 3 -N concentrations by 78%.…”
Section: Effects Of Additives In Trench Backfillsmentioning
confidence: 99%
“…The first attempts to apply such biotechnologies in tile drainage systems were performed in the U.S. (Blowes et al, 1994;Cooke et al, 2001;van Driel et al, 2006). Subsequently, later studies (Jaynes et al, 2008;Cameron and Schipper, 2010;Christianson et al, 2009Christianson et al, , 2011 suggested that application of "nature-driven" measures can substantially reduce NO 3 -N in drainage water. However, organic material is needed as a carbon source to promote the growth of heterotrophic denitrifying bacteria in bioreactors.…”
mentioning
confidence: 99%
“…Different materials and different processes are required to treat the two primary nutrients of concern in drainage waters. Reduction curtains and infiltration filters have been proposed to decrease nitrogen loads entering ditches (Jaynes et al 2008;Greenan et al 2006). With these approaches, trenches are filled with wood chips or other organic materials to create a "bioreactor" where enhanced denitrification can occur.…”
Section: Reactive Barriersmentioning
confidence: 99%
“…The crop production system employed, the amount, rate, and timing of fertilizer application, the size and arrangement of drainage tiles, and the presence of cover crops are all known to influence nitrogen inputs to surface waters from tile drainage systems (Kaspar et al, 2007;Kladivko et al, 2004;Nangia et al, 2008;deVos et al, 2000;Domagalski et al, 2008;Dinnes et al, 2002). Agronomic controls such as crop and fertilizer management, however, are not usually sufficient to rectify nutrient pollution resulting from tile drainage systems (Jaynes et al, 2008;Madramootro et al, 2007). Therefore, additional methods for nutrient removal and control are needed where subsurface tile drainage is common.…”
Section: )mentioning
confidence: 99%
“…A wide variety of treatment options for nutrient runoff have been developed. These include riparian buffer zones, biofilters, denitrification walls and constructed wetlands (Bezbaruah and Zhang, 2003;Darbi et al, 2003;Jaynes et al, 2008;Kelly et al, 2007;Lin et al, 2007;Su and Puls, 2007;Vymazal, 2007;Yamada et al, 2007). Although each of these systems has been shown to reduce the NO 3 -N concentration in groundwater, there is no single ideal system appropriate for use under all circumstances.…”
Section: Fig 4 Reactive (Ortho) Phosphate In Rvfb Effluentmentioning
confidence: 99%